Designing a Paradigmatic Model of Social Media in Addressing Environmental Issues of Electronic Waste in Iran - Rabiei, Maryam; Jafari, Ali; Basirian Jahromi, Hossein (Assessment and Practice in Educational Sciences, 2025)
The present study was conducted with the aim of designing a paradigmatic model of social media—specifically Instagram and X (formerly Twitter)—in addressing the environmental issues of electronic waste in Iran. From the perspective of its purpose, this research falls within the category of applied–developmental studies. The participants consisted of two groups of experts: theoretical experts (professors and researchers in the fields of media, communication, and environmental management with expertise in media marketing) and practical experts (managers and specialists working in waste management organizations and social media activists involved in the environmental issues of electronic waste). Using theoretical sampling and continuing the interview process until reaching theoretical saturation, a total of 12 participants were selected. Data analysis was conducted using the grounded theory method with the assistance of MaxQDA. The findings indicated that causal conditions (including political and legal awareness, socio-cultural, economic and commercial, and technological and innovative factors) provided the foundation for the emergence of the core phenomenon (i.e., the role of social media in representing environmental issues related to electronic waste). This phenomenon developed within the context of contextual conditions (such as the institutional structure of information dissemination and governmental policymaking) and under the influence of intervening conditions (such as the limitations and challenges of social media) in Iran. Under these circumstances, a set of strategies emerged—particularly the production and redistribution of environmental content on social media—which led to outcomes in three domains: improving the management and recycling of electronic waste, developing economic aspects related to recycling, and influencing policymaking and audience behavior change through the media. The findings of this study can provide an appropriate basis for media policymaking and environmental planning in the country.